Igre oko Vladimira Nabokova - recepcija Nabokova u njegovoj ulozi homo ludensa - Medarić, Magdalena (Array, 1996)
A discussian of historical reasons, in the period of last few decades, for the reception of the novelist in his role of a ludistic author. The views of critics and general public, together with the stratehies of the author himself are being taken into consideration.